(untitled) (Medico Legal Update, 2019)
Adolescence is a transitional stage of physical and psychological development that generally occurs during the period from puberty to legal adulthood. During transition from childhood to adulthood people are exposed to various hazards having potentiality to lead to unnatural deaths by distorting physical, mental and social wellbeing. Studying pattern of unnatural deaths helps stakeholders to formulate policies for prevention of loss of important human resource. The present study is a retrospective study undertaken in the Department of Forensic Medicine and Toxicology, Karnataka Institute of Medical Sciences, Hubballi, to determine the pattern of adolescents deaths (10-19 years) brought for autopsy during the period of January 2016 to December 2016. Total 82 cases were studied and it was observed that the incidence rate of adolescent deaths was 6.49% among which 43were males (52.43%) and 39 females (47.56%). Rural deaths were higher when compared to urban, accidental deaths were the highest and road traffic accidents followed by poisoning and burns were the commonest causes of deaths. In conclusion, behavior change communication of parents, teachers, career guides, office masters, law keepers etc. for fostering congenial environment for upbringings of adolescents is needed to prevent unnatural deaths.